WiFi-Nano : Reclaiming WiFi Efficiency through 800 ns slots - Magsiretti, Eugenio; Chintalapudi, Krishna; Radunovic, Bozidar; Ramjee, Ramachandran (Mobicom, 2011)
The increase in WiFi physical layer transmission speeds from 1 Mbps to 1 Gbps has reduced transmission times for a 1500 byte packet from 12 ms to 12 us. However, WiFi MAC overheads such as channel access and acks have not seen similar reductions and cumulatively contribute about 150 us on average per packet. Thus, the efficiency of WiFi has deteriorated from over 80% at 1 Mbps to under 10% at 1 Gbps. In this paper, we propose WiFi-Nano, a system that uses 800 ns slots to significantly improve WiFi efficiency. Reducing slot time from 9 us to 800 ns makes backoffs efficient but clear channel assessment can no longer be completed in one slot since preamble detection can now take multiple slots. Instead of waiting multiple slots for detecting preambles, nodes speculatively transmit preambles as their backoff counters expire while continuing to detect premables using self-interference cancellation. Upon detection of preambles from other transmitters, nodes simply abort their own preamble transmissions, thereby allowing the earliest transmitter to succeed. Further, receivers speculatively transmit their ack preambles at the end of packet reception, thereby reducing ack overhead. We validate the effectiveness of WiFi-Nano using an implementation on an FPGA based software defined radio platform and through extensive simulations, demonstrating efficiency gains of up to 100%.
(selected among top 5 contenders for best paper award)